Communication Competency Needs of Students with Autism Spectrum Disorder (ASD) : Teachers' Perspectives and Students' Abilities - Khoirunnisa, Azizah Nurul; Munir, Munir; Shahbodin, Faaizah; Dewi, Laksmi (LPPM Universitas Pendidikan Mandalika, 2025)
This study aims to analyze the communication competency needs of students with Autism Spectrum Disorder (ASD) based on teachers' perspectives and the communication abilities of the students themselves. A survey method with a quantitative approach was used, collecting data through questionnaires distributed to 41 teachers and 20 ASD students from Special Schools (SLB) in West Java. The sampling technique applied was purposive sampling. The data were analyzed using IBM SPSS Statistics version 23, with descriptive analysis techniques and reliability tests to ensure the validity of the instruments. The research results reveal that students with ASD need improvements in both receptive and expressive communication competencies, particularly in understanding multi-step instructions, recognizing visual symbols, and responding to non-verbal cues and complex questions. Furthermore, challenges were found in initiating conversations and using more specific vocabulary in social interactions. This study emphasizes the importance of developing more structured and individualized teaching strategies to enhance the communication competencies of students with ASD.